Optimization of Oil Adsorption Capacity by Aerogel Powder Synthesized Using Emulsion Droplets as Micro-reactors in Ambient Conditions from Sodium Silicate as Precursor - Cho, Young-Sang; Sung, Sohyeon; Woo, Seung Hee; Kim, Young Seok (Korean Journal of Metals and Materials, 2021)
In this study, silica aerogel particles were synthesized from emulsion droplets as micro-reactors at room temperature under ambient pressure. An economical precursor, sodium silicate, was used as the starting material for silica, and an emulsification technique was applied to form droplets in continuous phase. By controlling the composition of the dispersed phase using ammonium hydroxide, the effect of pH on the morphologies of the final aerogel particles was studied by SEM observation. As a demonstrative application, hydrophobic silica aerogel particles were produced by modification using a silane coupling agent, for oil adsorption. The amount of oil adsorbed by the aerogel particles was optimized by adjusting the concentration of precursors in the emulsion droplets, the composition of the dispersed phase, and the concentration of the coupling agent during surface treatment of the particles. The resulting aerogel particles were characterized using BET, TGA, and the contact angle of water droplets after modification using silane coupling agents with different carbon numbers. The optimized value of adsorbed silicone oil (100 CS) was measured to be about 250 % relative to the weight of the aerogel particles. For comparison, other types of porous silica particles were also prepared from emulsion-assisted self-assembly routes to quantify the amount of adsorbed oil.